Host specificity and pathogenicity test of Colletotrichum Spp. isolated from black pepper (Piper nigrum l.) anthracnose / Azrul Ezwan Shah Abdul Wahab - Abdul Wahab, Azrul Ezwan Shah (Faculty of Plantation and Agrotechnology, 2019)
Anthracnose is the fungal disease that affects many plants, including vegetables, fruits, and trees. It causes dark, sunken lesions on leaves, stems, flowers, and fruits. This study was conducted to determine the host specificity and pathogenicity of fungal pathogen isolated from black pepper anthracnose. Pathogenicity test was conducted on the leaves of black pepper, red chilli and bird’s eye chilli using mycelia plug technique. The study had identified Colletotrichum spp as the fungal pathogen of anthracnose disease. The black pepper, red chilli and bird’s eye chilli leaves became infected with Colletotrichum spp and developed symptoms. The symptoms start to appear on the wounded part of inoculated leaves on the fourth day after inoculation. On the 9th day after inoculation, dark brown lesions of anthracnose have already spread. Pathogenicity test using mycelia plug method showed that all representative isolates of Colletotrichum spp. were pathogenic on wounded treatments. Black pepper leaves produced highest disease severity index, 92.59% followed by bird’s eye chilli, 77.77% and red chilli, 70.37%. Hence, susceptibility presence with degree of virulence that ranges from low to very high. Unwounded and control treatment did not show any symptoms of anthracnose even after 9 days of inoculation. Morphological characteristics of the isolates re-isolated from the lesions were similar with morphological characteristics of Colletotrichum spp. isolates obtained from pure culture and thus Koch’s postulates were fulfilled.